2011
DOI: 10.4172/plastic-surgery.1000683
|View full text |Cite
|
Sign up to set email alerts
|

Ganglion cyst in children: Reviewing treatment and recurrence rates

Abstract: G anglion cysts are mucinous tumours that usually arise from underlying joint capsules or tendon sheaths, and are the most common soft tissue masses of the hand (1). Their pathogenesis remains controversial. The extracapsular part of the dorsal ganglia is well known, but little is known about the intracapsular component and its etiology. While a great deal of information exists for adult hand and wrist ganglia, there is a paucity of data for the pediatric population. Although they commonly occur as benign lesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 7 publications
0
14
1
Order By: Relevance
“…The prevalence of the ganglion cyst was reported higher in the female gender. [ 3 , 4 ] However, the rate was found to be equal for each gender (50%-50%) in our study. To our knowledge, there is no study reporting the Turkish pediatric population’s hand tumor distribution to compare our results.…”
Section: Discussioncontrasting
confidence: 70%
“…The prevalence of the ganglion cyst was reported higher in the female gender. [ 3 , 4 ] However, the rate was found to be equal for each gender (50%-50%) in our study. To our knowledge, there is no study reporting the Turkish pediatric population’s hand tumor distribution to compare our results.…”
Section: Discussioncontrasting
confidence: 70%
“…3 Precipitating trauma is also reported in 0% to 12% of pediatric case series. 5,9,13,16 One of the accepted theories is that ganglion cysts arise from modified synovial cells in response to minor trauma. Repetitive stretching of supporting joint structures stimulates hyaluronic acid production by fibroblasts at the synovial-capsule interface, resulting in mucin accumulation and formation of the ganglion cyst.…”
Section: Resultsmentioning
confidence: 99%
“…Ganglion cysts of the wrist can occur at any age, with patients as young as 2 months reported. 13 Due to significant heterogeneity within the patient populations of studies examining pediatric wrist ganglia, average reported patient ages range between 3 and 14 years, 5,8,12-14,17,20 with a slight bias to older ages in papers examining surgical management of ganglion cysts. As with adult ganglion cysts, there appears to be a slight female preponderance among pediatric populations, with a ratio of 1.4-2.7:1 (F:M).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations